Relationship of Appetite, Body Image, and Energy Intake with Body Mass Index in Undergraduate Students in Surakarta - Anita Febrian Permata Sari; Eti Poncorini Pamungkasari; Yulia Lanti Retno Dewi (Universitas Ahmad Dahlan, 2021)
Background: Young adults are vulnerable to lifestyle changes that will eventually change their behavior, including health behavior. Behavioral changes during this period can affect nutritional status. Nutritional status is affected by energy intake, influenced by several internal factors such as appetite and body image. This study shows the correlation between appetite, body image, and energy intake with body mass index. Method: This study was conducted with a random sampling method through 120 undergraduate students. Appetite was measured using a visual analog scale. Energy intake was measured using the 24-hour food recall method. Statistical analysis used was Spearman's rankBody shape perception was assessed using the Stunkard figure rating scale. Results: Appetite is closely related to energy intake (p <0.05) but not with BMI. Body image correlates with intake energy and BMI. Most obese students (70.4%) consider themselves overweight. Energy intake is correlated with BMI (p <0,001). Conclusion: Appetite and body image are related to food intake. Energy intake is correlated with body mass index.